Sarcopenia and major complications in patients undergoing oncologic colon surgery - Michael Schneider; Martin Hübner; Fabio Becce; Joachim Koerfer; Jean‐Aibert Collinot; Nicolas Demartines; Dieter Hahnloser; Fabian Grass; David Martin (Wiley, 2021)
Abstract Background Sarcopenia is a surrogate marker for malnutrition and frailty, which has been linked to higher complication rates and prolonged length of stay (LOS) after surgery. The study aim was to assess the correlation between computed tomography (CT)‐based sarcopenia and short‐term clinical outcomes after oncologic colon surgery. Methods This retrospective study included consecutive patients operated between May 2014 and December 2019. Three radiological indices of sarcopenia were measured at the level of the third lumbar vertebra on preoperative CT scans: skeletal muscle area (SMA), skeletal muscle index (SMI) (both markers of muscle quantity), and skeletal muscle radiation attenuation (SMRA) (marker of muscle quality). Patients with major complications (grade ≥ 3b according to the Clavien classification) were compared with those without. Statistical correlation between sarcopenia indices, LOS, and comprehensive complication index (CCI) was tested with the Pearson correlation coefficient. Results A total of 325 patients were included. Mean age was 67 years [standard deviation (SD) 14.3], mean body mass index was 26.0 kg/m2 (SD 5.3), and 193 (59%) were male. Fifty patients (15.4%) had major complications, while 275 (84.6%) did not. Patients with major complications had more open surgery (52 vs. 21%, P < 0.01), intraoperative blood loss (257 vs. 102 mL, P = 0.035), and intraoperative complications (22 vs. 9%, P = 0.012). Patients with major complications had significantly increased CCI scores (53 vs. 6, P < 0.01), reoperations (74 vs. 0%, P < 0.01), and LOS (33 vs. 7, P < 0.01). SMA and SMI were comparable between both groups (126.0 vs. 125.2 cm2, P = 0.974, and 43.4 vs. 44.3 cm2/m2, P = 0.636, respectively), while SMRA was significantly lower in patients with major complications (33.6 vs. 37.3 HU, P = 0.018). A lower SMRA was correlated with prolonged LOS (r = −0.207, P < 0.01) and higher CCI (r = −0.144, P < 0.01), while the other sarcopenia indices had no influence on surgical outcomes. Conclusions Muscle quality (SMRA) as a specific sarcopenia marker was lower in patients with major complications and seems to prevail over muscle quantity (SMA and SMI) in the prediction of adverse outcomes after oncologic colon surgery.